Evaluation of the Role of Exosome-derived MiRNA in Breast Cancer Diagnosis: A Systematic Review and Meta-analysis - Pezhman Ghadami; Neda Mehrafar; Maryam Hassanpour Amnieh; Fatemeh Rabiee; Mandana Ebrahimi; Hamed Rouzbahani (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Considering the importance of early detection of breast cancer and the use of non-invasive methods, the present study was conducted to evaluate the role of exosome-derived miRNA in breast cancer diagnosis. Material and methods: In the present systematic review and meta-analysis, information about exosome-derived miRNA in breast cancer diagnosis in all articles published up until the end of July 2023 was collected by two trained researchers individually using keywords and combinations of keywords from databases PubMed, Scopus, Science Direct, ISI, Web of Knowledge, Elsevier, Wiley, and Embase and Google Scholar. STATA (version 17) was used to analyze data using the fixed effects model in meta-analysis; p values less than 0.05 were considered significant. Results: A total of six studies were included in the meta-analysis process. The sensitivity and specificity of plasma-based exosomal miRNAs were 68% (ES, 95% CI: 0.39, 0.97) and 82% (ES, 95% CI: 0.52, 1.11), respectively. The sensitivity and specificity of serum-based exosomal miRNAs were 67% (ES, 95% CI: 0.33, 1.01) and 88% (ES, 95% CI: 0.54, 1.22), respectively. Conclusions: Exosomal miRNAs have high sensitivity and specificity in breast cancer diagnosis and can be considered a valuable and promising tool for early detection of breast cancer non-invasively.